Contesting the termite hypothesis for the origins of heuweltjies in Clanwilliam, South Africa - Innes, Sheona (Department of Biological Sciences, 2017)
The age and origins of large earth mounds (locally termed "heuweltjies") is under debate, with ages being proposed for between 4500 and 30 000 years old, and hypotheses including zoogenic and geological origins of the mounds. The widely accepted hypothesis for the origins of the heuweltjies found in the South Western Cape of South Africa is that mounds are ancient termitaria, belonging to the southern harvester termite Microhodotermes viator. Our idea was to use rocks and stone layer profiles to determine approximate ages of the heuweltjies as well as to gather evidence to either support or refute the termite hypothesis. We excavated ten mounds in Clanwilliam, South Africa, to gather stone and rock profiles throughout the mounds, as well as digging a trench through a heuweltjie with bedrock as its matrix in order to determine the extent of the bedrock into the mound. No stone layers as such were found. What we did find was that the mounds are a whole order of magnitude greater in volume than large termite mounds made by the northern harvester termite Macrotermes in tropical regions, and many of the mounds contain large rocks both throughout the mound as well as on the surface. The trench cut through the mound on bedrock revealed the bedrock extending all the way to the centre of the mound, on the same level as the surface of the surrounding matrix. This evidence can be used to refute the termite hypothesis for the heuweltjies of Clanwilliam as it is virtually impossible for termites to move rocks up to 25 kg to the top of a mound, and mining soil from beneath a mound with bedrock at its base is an impossibility.